2019
DOI: 10.1038/s41598-019-54879-4
|View full text |Cite
|
Sign up to set email alerts
|

Childhood motor performance is increased by participation in organized sport: the CHAMPS Study-DK

Abstract: Evidence suggests that motor performance in children is declining globally. We tested whether participation in organized sport is associated with motor performance, and estimate the effect of 30 months participation in organized sport on motor performance. Study participants were 1067 primary school students, enrolled in the Danish Childhood Health, Activity, and Motor Performance School study. Participation in organized sport was reported via text messaging. Coordination-related motor performance composite, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
4
12
0
8
Order By: Relevance
“…Recent findings from the Vallence et al [82] CHAMPS Study-DK complement the current study's findings, showing that weekly participation in organised sport over a 30 month period from 1067 Danish school-aged children (6 to 12 years) is positively associated with motor performance across the coordination fitness spectrum. Further to this, Bryant et al [83] found that a 1 day per week PE intervention, focusing on FMS, resulted in the improvement of motor skills in children (mean age ± SD = 8.3 ± 0.4 years) within the intervention group (n = 82) relative to children in the control group (n = 83).…”
Section: Discussionsupporting
confidence: 81%
“…Recent findings from the Vallence et al [82] CHAMPS Study-DK complement the current study's findings, showing that weekly participation in organised sport over a 30 month period from 1067 Danish school-aged children (6 to 12 years) is positively associated with motor performance across the coordination fitness spectrum. Further to this, Bryant et al [83] found that a 1 day per week PE intervention, focusing on FMS, resulted in the improvement of motor skills in children (mean age ± SD = 8.3 ± 0.4 years) within the intervention group (n = 82) relative to children in the control group (n = 83).…”
Section: Discussionsupporting
confidence: 81%
“…La psicología deportiva es una disciplina de carácter interconductual, que asesora al deportista y gestiona dicho asesoramiento, trabajando de forma continuada durante toda la temporada 6 . Estudia las variables psicológicas de iniciación deportiva en los niños, trabajando directamente con los deportistas, solucionando problemas, controlando la ansiedad y los miedos, la concentración y el entorno deportivo allí donde aparecen las respuestas emocionales 3,7 .…”
Section: Resultados 1ª Pregunta ¿Qué Es Psicología Deportiva?unclassified
“…Especialmente en niños y jóvenes, la psicología deportiva desarrolla el potencial del joven 6 . En este contexto, el psicólogo deportivo no es un psicólogo que trabaja en deporte, sino que es un profesional que aplica sus profundos conocimientos científicos de la psicología al estudio del comportamiento humano [9][10][11] .…”
Section: Resultados 1ª Pregunta ¿Qué Es Psicología Deportiva?unclassified
See 1 more Smart Citation
“…O Desempenho Motor (DM) pode ser definido como a combinação de habilidades motoras fundamentais e os seus componentes relacionados à aptidão físico-motora (VALLENCE et al, 2019). Sabe-se que o DM é importante para o aprimoramento físico, psíquico e social tanto de crianças quanto de adolescentes, permitindo que desenvolvam um estilo de vida mais ativo quando adultos, sendo complacente para a prática de atividades físicas diversas e o desenvolvimento de habilidades esportivas específicas.…”
Section: Introductionunclassified